1995
DOI: 10.1083/jcb.131.6.1677
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pore complex clustering and nuclear accumulation of poly(A)+ RNA associated with mutation of the Saccharomyces cerevisiae RAT2/NUP120 gene.

Abstract: • Abstract. To identify genes involved in the export of messenger RNA from the nucleus to the cytoplasm, we used an in situ hybridization assay to screen temperature-sensitive strains of Saccharomyces cerevisiae. This identified those which accumulated poly(A) ÷ RNA in their nuclei when shifted to the non-permissive temperature of 37°C. We describe here the properties of yeast strains carrying mutations in the RA T2 gene (RA Tribonucleic acid trafficking) and the cloning of the RA T2 gene. Only a low percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
136
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 80 publications
8
136
1
Order By: Relevance
“…In nup159 cells, the phenomenon is actually the opposite of that in gle2 cells: nup159 NPCs are clustered at 23°C, whereas at 37°C their distribution is over the entire nuclear surface (Gorsch et al, 1995). The herniated clustered NPCs in gle2 cells are distinct from the successive interconnected NPCs found in grape-like aggregates of constitutively clustered NPCs in nup145, nup120, nup84, and nup85 mutant cells (Wente and Blobel, 1994;Aitchison et al, 1995a;Heath et al, 1995;Goldstein et al, 1996;Siniossoglou et al, 1996). Cells deleted for NUP116 form herniations when shifted to the restrictive temperature (Wente and Blobel, 1993 (Wente and Blobel, 1993).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In nup159 cells, the phenomenon is actually the opposite of that in gle2 cells: nup159 NPCs are clustered at 23°C, whereas at 37°C their distribution is over the entire nuclear surface (Gorsch et al, 1995). The herniated clustered NPCs in gle2 cells are distinct from the successive interconnected NPCs found in grape-like aggregates of constitutively clustered NPCs in nup145, nup120, nup84, and nup85 mutant cells (Wente and Blobel, 1994;Aitchison et al, 1995a;Heath et al, 1995;Goldstein et al, 1996;Siniossoglou et al, 1996). Cells deleted for NUP116 form herniations when shifted to the restrictive temperature (Wente and Blobel, 1993 (Wente and Blobel, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, protein import was not noticeably diminished. This suggested that Gle2p is specifically required for a NPC export func- (Wente and Blobel, 1993;Bogerd et al, 1994;Doye et al, 1994;Aitchison et al, 1995a;Gorsch et al, 1995;Heath et al, 1995;Li et al, 1995;Goldstein et al, 1996;Siniossoglou et al, 1996).…”
Section: Gle2 Is Required For Poly(a)+ Rna Exportmentioning
confidence: 99%
See 2 more Smart Citations
“…The deletion or immunodepletion of any nup from these complexes has dramatic consequences on the architecture and function of the NPC, as well as on the organization of the nuclear envelope (17,20,(23)(24)(25)(26). In particular, Nup120 is involved in nuclear poly(A) ϩ mRNA and preribosome export, NPC assembly and distribution, and nuclear envelope organization (26)(27)(28).…”
mentioning
confidence: 99%